APOL1 Induces Pyroptosis of Fibroblasts Through NLRP3/Caspase-1/GSDMD Signaling Pathway in Ulcerative Colitis - Zhu F; Li S; Gu Q; Xie N; Wu Y (Dove Medical Press, 2023)
Fangqing Zhu,1 Sheng Li,2 Qiuping Gu,1 Ningsheng Xie,1 Yinxia Wu3 1Department of Gastroenterology, Ganzhou People's Hospital, Ganzhou, Jiangxi, 341000, People's Republic of China; 2Department of Gastroenterology, Yuebei People's Hospital, Shantou University Medical College, Shaoguan, Guangdong, 512026, People's Republic of China; 3Department of Rehabilitation, Ganzhou People's Hospital, Ganzhou, Jiangxi, 341000, People's Republic of ChinaCorrespondence: Fangqing Zhu; Yinxia Wu, Email wanliqingkong0707@163.com; xiaflora0608@163.comBackground: Pyroptosis is a form of proinfammatory gasdermin-mediated programmed cell death. Abnormal infammation in the intestine is a critical risk factor for Ulcerative colitis (UC). However, at present, it is not clear whether pyroptosis of colonic fibroblasts is involved in the pathogenesis and progression of UC.Methods: In this study, key genes associated with UC were identified by bioinformatics analysis. Datasets were downloaded from the Gene Expression Omnibus (GEO) database (GSE193677). The differentially expressed genes were analyzed, and the hub genes were screened by weighted gene co-expression network analysis (WGCNA) and differentially expressed genes. We also downloaded the dataset from GEO for single-cell RNA sequencing (GSE231993). The expression of key genes was verified by immunohistochemistry, immunofluorescence and Western blot, and the specific pathways of key genes inducing pyroptosis in cell lines were explored.Results: The results of bioinformatics analysis showed that the expression of APOL1 and CXCL1 in UC tissues was significantly higher than that in normal tissues. The results of single-cell analysis showed that the two genes were co-localized to fibroblasts. These results were consistent with the results of immunohistochemistry and immunofluorescence colocalization in human intestinal mucosa specimens. Furthermore, APOL1 overexpression induced NLRP3-caspase1-GSDMD-mediated pyroptosis of fibroblasts, which was confirmed by Western blot.Conclusion: APOL1 induces pyroptosis of fibroblasts mediated by NLRP3-Caspase1-GSDMD signaling pathway and promote the release of chemokines CXCL1. Fibroblasts may play a crucial role in the pathogenesis and progression of UC.Keywords: apolipoprotein L1, pyroptosis, fibroblasts, gasdermin-D, Ulcerative colitis